Dreaming big: On expanding dreams, hubris, and the character of the biblical Joseph - Rabel, Magnus (Journal for the study of the Old Testament, 2024)
Dreams play a special role in the Joseph narrative. They are arranged in three pairs each and carry the story forward decisively. Joseph’s dreams in particular form a narrative framework for the central theme of the story: family conflicts and dominion. Again and again, it has been observed that while Joseph’s first dream comes true, his second does not correspond entirely to the events that transpire within the narrative. Contrary to the tendency to make this second dream equal to the first, or to exclude or reinterpret it in terms of literary criticism, this essay proposes that the second dream should be understood within the negative conception of the Joseph character in Genesis 37 as a sign of Joseph’s hubris and therefore as an exaggeration or even invention which Joseph himself manufactured.